Nalar Kemanusiaan dalam Da’wah Multikultural: - Yulianto, Hendra Bagus (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
Islam taught by Allah as well as being exemplified by the Prophet is a universal teaching which is manifested through the tagline Islam rahmatan lil alamin, being able to give grace to anyone, including the society where da'wah entity is carried out. But in reality there is a gap where das sein da'wah which is practiced not only hasn't been able to answer social problems in the society, but also it has also contributed to creating problems, that is violence in the name of religion. The dynamics of this issue are very vulnerable, especially in the context of a multicultural society whose existence is built on the foundation of diversity. This research wants to offer an alternative approach in humanist da'wah, especially in formulating da'wah messages by making humanity values as as humanist perspective in a multicultural society. Humanity values are expected to be able to become a da'wah approach, especially in the context of a multicultural society, including: the value of truth, the value of virtue (right conduct), the value of non-violence , the value of love or love, and the value of peace